“TRANSLATION OF RELIGIOUS TEXTS PROBLEMS AND SPECIFICITIES” - Abdialimova Lobar Gaybulla qizi, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Annotation. The translation of sacred and religious texts presents unique and complex  challenges  that  extend beyond typical  linguistic transfer,  engaging  deeply with theology, culture, and social belief. This article explores the specific problems encountered in this field, particularly the tension between formal fidelity to the source text (literal meaning and structure) and dynamic equivalence (conveying the original effect and message in the target culture). Key issues include handling archaic language, non-equivalent culture-specific terms, preserving the text's sacredness and rhetorical features, and managing the potential for ideological manipulation by translators. The study utilizes descriptive and comparative methods to analyze common challenges and the corresponding strategies employed by scholars and practitioners.